2017
DOI: 10.1039/c6ta10757e
|View full text |Cite
|
Sign up to set email alerts
|

MnO2 nanoflowers and polyaniline nanoribbons grown on hybrid graphene/Ni 3D scaffolds by in situ electrochemical techniques for high-performance asymmetric supercapacitors

Abstract: MnO2 nanoflowers and polyaniline nanoribbons on nickel–graphene foams for supercapacitors provide an energy density of 41.0 W h kg−1 at 787.3 W kg−1.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 55 publications
(14 citation statements)
references
References 57 publications
0
14
0
Order By: Relevance
“…The electrodes and membranes were overlapped and packaged by ultra-thin plastic film. Obviously, the maximum energy density of PANI-Mn supercapacitor is 51.38 Wh kg −1 at the power density of 850 W kg −1 , presenting a higher energy density and power density compared to analogous PANI supercapacitors, such as NPCNFs//NPCNFs (NPCNF means nitrogen-doped porous carbon nanofibers, 9.2 Wh kg −1 at 0.25 kW kg −1 ), [50] rGO/PANI (28.06 Wh kg −1 at 0.25 kW kg −1 ), [51] MnO 2 /HGNF// PANI/HGNF (HGNF means hybrid graphene/Ni 3D scaffolds, 41.0 W h kg −1 at 787.3 W kg −1 ), [52] MnO 2 @PANI// MnO 2 @PANI (37 Wh kg −1 at 386 W kg −1 ), [19] SPAN/FC// SPAN/FC (SPAN means self-doped polyaniline, 9.2 Wh kg −1 at 1000 W kg −1 ), [53] BNC/CNT/ion gel (BNC means bacterial Slight polarization is observed when the voltage range expands from 1.5 to 1.8 V. The PANI-Mn supercapacitor is investigated at the voltage window of 1.7 V. Figure 8C,D shows CV curve at different scanning rates and GCD curve at different current densities.…”
Section: Wwwadvelectronicmatdementioning
confidence: 99%
“…The electrodes and membranes were overlapped and packaged by ultra-thin plastic film. Obviously, the maximum energy density of PANI-Mn supercapacitor is 51.38 Wh kg −1 at the power density of 850 W kg −1 , presenting a higher energy density and power density compared to analogous PANI supercapacitors, such as NPCNFs//NPCNFs (NPCNF means nitrogen-doped porous carbon nanofibers, 9.2 Wh kg −1 at 0.25 kW kg −1 ), [50] rGO/PANI (28.06 Wh kg −1 at 0.25 kW kg −1 ), [51] MnO 2 /HGNF// PANI/HGNF (HGNF means hybrid graphene/Ni 3D scaffolds, 41.0 W h kg −1 at 787.3 W kg −1 ), [52] MnO 2 @PANI// MnO 2 @PANI (37 Wh kg −1 at 386 W kg −1 ), [19] SPAN/FC// SPAN/FC (SPAN means self-doped polyaniline, 9.2 Wh kg −1 at 1000 W kg −1 ), [53] BNC/CNT/ion gel (BNC means bacterial Slight polarization is observed when the voltage range expands from 1.5 to 1.8 V. The PANI-Mn supercapacitor is investigated at the voltage window of 1.7 V. Figure 8C,D shows CV curve at different scanning rates and GCD curve at different current densities.…”
Section: Wwwadvelectronicmatdementioning
confidence: 99%
“…[11] Generally,e fficient transfer of the charge carriers across the semiconductor interface is key for photocatalytice fficiency,a nd the heterostructure is beneficial to the interfacial charget ransfer. [31][32][33] Thus the photocatalytic activity can be significantly enhanced. Figure 6a shows the periodic on/off photocurrentr esponse of all samples under visible light.…”
Section: Resultsmentioning
confidence: 99%
“…In inorganics/rGO composites, the improvement of capacitance is largely attributed to the conversion of mechanism so that the importance of extensive contact with electrolytes has declined. The materials with metallic element have higher specific capacitance due to active redox reactions, including Ni, Mo, Mn, Ti, Co, and others. For example, Chen et al showed that the sulfated NiMn‐layered double hydroxides/rGO composite as electrodes had enhanced performance in supercapacitor .…”
Section: Graphene For Rechargeable Batteriesmentioning
confidence: 99%